2021
DOI: 10.1099/ijsem.0.004986
|View full text |Cite
|
Sign up to set email alerts
|

Cyberlindnera dasilvae sp. nov., a xylitol-producing yeast species isolated from rotting wood and frass of cerambycid larva

Abstract: Six yeast isolates were obtained from rotting wood samples in Brazil and frass of a cerambycid beetle larva in French Guiana. Sequence analysis of the ITS-5.8S region and the D1/D2 domains of the large subunit rRNA gene showed that the isolates represent a novel species of Cyberlindnera. This novel species is related to Cyberlindnera japonica, Cyberlindnera xylosilytica, Candida easanensis and Candida maesa. It is heterothallic and produces asci with two or four hat-shaped ascospores. The name Cyberlindnera da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…shehatae (both present in our samples), and some members of the genus Spathaspora are considered prominent species for the conversion of xylose to ethanol (Cadete & Rosa, 2018; Cadete et al, 2015; Morais et al, 2020). Among other species we reported here, C. tropicalis , C. intermedia , C. maltosa , and species of the genera Cyberlindnera , Sugiyamaella , Wickerhamomyces , Meyerozyma , and Pichia were also reported to ferment xylose into ethanol and/or xylitol (Barros et al, 2021; Bazoti et al, 2017; Geijer et al, 2020; Morais et al, 2020; Narisetty et al, 2021; Sena et al, 2017).…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…shehatae (both present in our samples), and some members of the genus Spathaspora are considered prominent species for the conversion of xylose to ethanol (Cadete & Rosa, 2018; Cadete et al, 2015; Morais et al, 2020). Among other species we reported here, C. tropicalis , C. intermedia , C. maltosa , and species of the genera Cyberlindnera , Sugiyamaella , Wickerhamomyces , Meyerozyma , and Pichia were also reported to ferment xylose into ethanol and/or xylitol (Barros et al, 2021; Bazoti et al, 2017; Geijer et al, 2020; Morais et al, 2020; Narisetty et al, 2021; Sena et al, 2017).…”
Section: Resultsmentioning
confidence: 70%
“…Similarly, C. albicans is known as a human commensal and opportunistic pathogen, but it is sporadically found on plant materials (Bensasson et al, 2019; Lachance et al, 1923; Opulente et al, 2019). Cyberlindnera species are frequently recovered from this type of substrate (Barros et al, 2021; Boontham et al, 2017). In this study, we found two new species belonging to this clade.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations